The Devil on the Entrepreneur’s Shoulder: Analyzing the Relationship Between Moral Disengagement, Founders’ Motives, and Unethical Behavior of Entrepreneurs on Social Media - Baccarella, Christian; Scheiner, Christian; et al. (Understanding Social Media and Entrepreneurship. Exploring Diversity in Entrepreneurship, 2020)
For quite some time now, research has discussed the importance of social media in the corporate context. Due to their simplicity and cost efficiency, social media applications are also particularly attractive for entrepreneurs. However, studies on social media have mainly concentrated on the benefits. Besides the many advocated advantages of social media, there are also many critical issues which can lead to negative consequences for users. Recent corporate social media–related scandals illustrate this and sparked a public discourse regarding ethically appropriate behavior of companies on social media. Using social media in an inappropriate way can have devastating consequences for a company, which can be especially fatal for young ventures. This chapter seeks to explore why especially entrepreneurs may lower their moral standards on social media and behave unethically. We find that the concept of moral disengagement can explain this negative behavior. We also find that entrepreneurs’ attention to economic goals is positively related to moral disengagement, whereas entrepreneurs’ attention to ethical responsibilities is negatively related to moral disengagement. We discuss implications for theory, practice, and future researc
Keywords: Dark side; Entrepreneurial motives; Mediation; Moral disengagement; Social networking sites; Regression; Unethical behavior